And the mountains echoed - Hosseini, Khaled (India : bloomsbury, 2013)
A novel about how people love, how they take care of each other, and how choices made today can resonate through future generations. Author Khaled Hosseini gives listeners a multi-generational family story revolving around siblings and how they love, betray, hurt, honor, and would do anything for one another.
Morsheda Aktar
Keywords: Families -- Fiction; Interpersonal relations -- Fiction; Community life -- Fiction; Historical fiction